Comparative Clinical-Imaging and Histogenetic Analysis Between Astrocytoma IDH-Mutant Grade 4 and Glioblastoma IDH-Wildtype—Is There Really a Worse One? - Cristian Ionut Orasanu; Mariana Aschie; Mariana Deacu; Madalina Bosoteanu; Sorin Vamesu; Manuela Enciu; Georgeta Camelia Cozaru; Anca Florentina Mitroi; Sinziana Andra Ghitoi; Ana Maria Cretu; Oana Andreea Ursica; Raluca Ioana Voda (Diagnostics, 2025)
Background: Brain tumors pose a significant health threat, leading to high morbidity and mortality rates. Astrocytoma IDH-mutant grade 4 (A4IDHmt) and glioblastoma IDH-wildtype (G4IDHwt) exhibit similar clinical and imaging characteristics. This study aims to highlight the differences in their clinical evolution and histogenetic aspects with the possible therapeutic impact, as well as the adverse prognostic factors in patient survival. Methods: We performed a 10-year retrospective study of grade 4 gliomas, evaluating immunomarkers and FISH tests. We also quantified tumor necrosis and microvascular density. Results: A total of 81 cases were identified; 54.32% were A4IDHmt. We observed that A4IDHmt patients were younger (34.10% under 50) and had a higher survival rate (4.55%). This group also exhibited a more pronounced microvascular density (p = 0.010) and proliferative index (p = 0.026). G4IDHwt was associated with larger tumor volumes (94.84 cm3 vs. 86.14 cm3), lower resectability rates (82.88% vs. 87.67%), and a more significant immature cell population (83.78% vs. 68.18%). In the case of both, the negative risk on survival in the univariate analysis is given by advanced age (A4IDHmt: HR = 1.035, G4IDHwt: HR = 1.045) and p53 immunopositivity (A4IDHmt: HR = 6.962, G4IDHwt: HR = 4.680). Conclusions: The negative risk factors for A4IDHmt include the rapid onset of clinical symptoms (HR = 2.038), diabetes mellitus (HR = 2.311), arterial hypertension (HR = 2.325), residual tumor (HR = 2.662), increased residual tumor volume (HR = 1.060), increased microvascular density (HR = 1.096), and high tumor necrosis (HR = 1.097). For G4IDHwt, the negative risk factors consist of increased residual volume (HR = 1.023), lost PTEN immunoreaction (HR = 33.133), and unmethylated DNA status (HR = 6.765, respectively HR = 20.573). Even if it has more risk factors, A4IDHmt is the lesser evil.